THE CHARACTERIZATION OF SEVERAL METAL IONS TOWARDS THE ENZYME TRYPSIN ACTIVITY - Das Salirawati (Jurnal Penelitian Saintek, 2016)
This study was aimed at determining the optimal conditions of the trypsine enzyme and the effect of metal ion Ag + (in the form of AgNO 3 ), metal ion Cu  (in the form of CuCl 2 ), K +  metal ions (in the form of KHPO 4 ), and ion Metal Zn  (in the form of ZnSO ) in various concentrations towards trypsin enzyme activity using casein substrate. The activity of trypsin enzyme was determined by Anson method in optimum conditions. The data were analyzed using qualitative descriptive. The results show that the activity of trypsin enzyme with substrate casein 10mg/mL in pH 8.37°C, incubation time of 20 minutes with the additional of ion (Ag 4 , Zn 2+ , K  2+ +, Cu2+) at various concentrations. Based on the research results, it was empirically proven that they were tendency of Ag + + dan Cu 2+to act as inhibitors and metal ions Zn 2+ and K + 2+  to act as activators to trypsine enzyme activity at casein substrat.